2006
DOI: 10.3354/dao068131
|View full text |Cite
|
Sign up to set email alerts
|

Interactions among two strains of Tubifex tubifex (Oligochaeta: Tubificidae) and Myxobolus cerebralis (Myxozoa)

Abstract: Host -parasite interactions influence host population growth, host evolution and parasite success. We examined the interactions among Myxobolus cerebralis, the parasite that causes salmonid whirling disease, and resistant and susceptible strains of the oligochaete host Tubifex tubifex. Strains of T. tubifex with diverse genotypes often coexist in nature and have variable susceptibilities to M. cerebralis infection. Further, parasite proliferation differs by several orders of magnitude among T. tubifex strains.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 47 publications
3
20
1
1
Order By: Relevance
“…In the current study, we suggest that similar effects in reducing overall parasite infectivity with M. cerebralis may occur even when cohabiting different phenotypes from the same lineage. A reduction in parasite production (TAMs released) with mixed T. tubifex lineages was not observed in a study reported by Steinbach-Elwell et al (2006). A key difference between that study and those of Beauchamp et al (2006) and that in our current study was duration of exposure of oligochaetes to the myxospores.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…In the current study, we suggest that similar effects in reducing overall parasite infectivity with M. cerebralis may occur even when cohabiting different phenotypes from the same lineage. A reduction in parasite production (TAMs released) with mixed T. tubifex lineages was not observed in a study reported by Steinbach-Elwell et al (2006). A key difference between that study and those of Beauchamp et al (2006) and that in our current study was duration of exposure of oligochaetes to the myxospores.…”
Section: Discussioncontrasting
confidence: 53%
“…Variations in susceptibility to M. cerebralis are known to occur among populations of lineage III T. tubifex originating from diverse geographic locations among strains that generally have shown significant genetic differences (e.g., by RAPD; Stevens et al 2001;Beauchamp et al 2002Beauchamp et al , 2005Kerans et al 2004) and even among genetically similar populations of lineage III oligochaetes (Rasmussen et al 2007). The severity of infections to M. cerebralis is most often assessed by the production and enumeration of TAMs released from T. tubifex over a defined period after exposure to myxospores (Gilbert and Granath 2001;Stevens et al 2001;MacConnell and Vincent 2002;Kerans et al 2004;Beauchamp et al 2005Beauchamp et al , 2006Steinbach-Elwell et al 2006). Infections with the parasite can also be assessed in the oligochaete by detection of M. cerebralis DNA by PCR or in situ hybridization, with the advantage that the latter method allows observation of developmental stages of the parasite beneath the intestinal mucosa of the worm (Antonio et al 1998;Rognlie and Knapp 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infection in T. tubifex may persist for the duration of the worm's lifespan and release of TAMs can occur periodically over the span of at least a few years (Gilbert & Granath 2001). Infected worms suffer from suppressed feeding, reduced growth (Stevens et al 2001, Kerans et al 2004, Steinbach Elwell et al 2006, Rasmussen et al 2008) and inhibited reproductive development (Shirakashi & El-Matbouli 2009), though no obvious parasite effects on survival have been shown (Shirakashi & El-Matbouli 2009). Several studies have revealed the importance of environmental factors such as temperature and substrate (Kerans & Zale 2002) and water flow ) on the establishment and development of the parasite within T. tubifex.…”
Section: Introductionmentioning
confidence: 99%
“…There are multiple genetic lineages (I-VI) of T. tubifex (Sturmbauer et al, 1999;Beauchamp et al, 2001;Crottini et al, 2008) that can be distinguished with the use of mitochondrial (16S) and genomic (18S and ITS) DNA sequences. Susceptibility of T. tubifex lineages to infection by the myxospores of M. cerebralis ranges from highly susceptible (Lineage III) and moderately susceptible (Lineage I), to completely resistant (Lineages V and VI; Stevens et al, 2001;Beauchamp et al, 2002;Steinbach et al, 2006;Arsan et al, 2007;Rasmussen et al, 2008). Although much of the work identifying genetic lineages of T. tubifex is based on the mitochondrial 16S rDNA gene, it is unlikely that this gene directly confers resistance to the parasite (Arsan et al, 2007).…”
mentioning
confidence: 99%